1966
DOI: 10.1002/prac.19660340115
|View full text |Cite
|
Sign up to set email alerts
|

Organische Schwefelverbindungen. 63. Zur Chemie des Thiocyclohexanons

Abstract: InhaltsiibersichtDas tiefrote, leicht polymerisierende monomere Thiocyclohexanon (1 a) steht im Gleichgewicht mit dem stabileren Enthiol I b, das durch Destillation des Tautomerengemisches I nahezu rein anfiillt. Fur Polgereaktionen ist es belanglos, ob man von I a oder I b ausgeht. Elektrophile Agenzien greifen I susschlieDlich am Schwefel an iind fdhren zu S-substituierten Cyclohexen-(1)-yl-mercaptanen. Nucleophile Partner geben mit I Produkte, die vorwiegend denen des Cyclohexanons entsprechen, sich in der … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1967
1967
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It is well known that thioketones more readily undergo reactions with nucleophilic reagents than do ketones [6] and are thus important intermediates. mary [21][22][23] and secondary amines [24] and diamines, [25] leading to Schiff bases or their tautomers, respectively. [17,18] Nevertheless, no method starting from sulfur analogues of carbonyl derivatives have been mentioned in the leading comprehensive monographs [1,19,20] devoted to enamine chemistry and synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that thioketones more readily undergo reactions with nucleophilic reagents than do ketones [6] and are thus important intermediates. mary [21][22][23] and secondary amines [24] and diamines, [25] leading to Schiff bases or their tautomers, respectively. [17,18] Nevertheless, no method starting from sulfur analogues of carbonyl derivatives have been mentioned in the leading comprehensive monographs [1,19,20] devoted to enamine chemistry and synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent titrations of these sensors with zinc-(II) acetate showed that compound 6a has the best working range of zinc concentrations with K d = 3.77 00 Ϯ 0.51 μM. mary [21][22][23] and secondary amines [24] and diamines, [25] leading to Schiff bases or their tautomers, respectively. Usually, these reactions are carried out with an equimolar ratio of reactants in alcoholic or toluene solution at reflux.…”
Section: Introductionmentioning
confidence: 99%
“…the quaternary centres C1 and C, is the primary process. For convenience 5 was estimated as the cyclic trimer 6, but the nonquantitative conversion of monomer to trimer has been noted previously (18,19); the yields of 4 and 5 reported in Table 1 are thus minimal. The temperature used for the thermolysis was not necessarily optimal and a knowledge of the reaction temperature profile seemed desirable.…”
Section: H Gwynne Giles Robertmentioning
confidence: 99%